2016
DOI: 10.1007/s10461-016-1356-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating HIV Infection and HIV Incidence Among Chinese Men Who Have Sex with Men with Recent Sexual Debut, Chongqing, China, 2011

Abstract: HIV among men who have sex with men (MSM) with recent male-male sexual debut, such as within the past five years, may be a proxy for recent HIV infection. Using this definition, we explored factors associated with HIV infection in this group to understand the evolving HIV epidemic among MSM in Chongqing. We conducted a cross-sectional respondent-driven sampling (RDS) survey among Chongqing MSM in 2011. Computer-assisted, self-administered questionnaires were used and blood specimens were collected for HIV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Regardless of sex of first partner, we also found that earlier age of sexual debut was associated with an increased likelihood of having more frequent condomless sex, having more lifetime sexual partners and being infected with HIV or syphilis. Our observation of the associations between earlier age of sexual debut and later risky sexual behaviors are consistent with other studies among both MSM and general populations [19, 21, 27, 28]. …”
Section: Discussionsupporting
confidence: 92%
“…Regardless of sex of first partner, we also found that earlier age of sexual debut was associated with an increased likelihood of having more frequent condomless sex, having more lifetime sexual partners and being infected with HIV or syphilis. Our observation of the associations between earlier age of sexual debut and later risky sexual behaviors are consistent with other studies among both MSM and general populations [19, 21, 27, 28]. …”
Section: Discussionsupporting
confidence: 92%
“…More prominent efficacy was found among participants who had higher educational attainment, were single, and had less income. Past studies suggested that lower socioeconomic status MSM were disproportionately affected by HIV [6, 34]. Meanwhile, same-sex marriage isn’t legal in China, MSM who are marred to women may have less access to HIV care services [6, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative meta-analysis Men (n) Kreiss et al (1993) 73 Kumta et al (2002) 81 Tabet et al (2002) 86 Golden et al (2003) 67 Buchbinder et al (2005) 63 Millett et al (2007) 78 Millett et al (2007) 78 Reisen et al (2007) 83 Mor et al (2007) 79 Sanchez et al (2009) 84 Templeton et al (2009) 87 Gust et al (2010) 69 McDaid et al (2010) 77 Jameson et al (2010) 71 Jozkowski et al (2010) 72 Zou et al (2010) 91 Sánchez et al (2011) 85 Chen et al (2011) 64 Lane et al (2011) 76 Oster et al (2011) 80 Thornton et al (2011) 89 Lan et al (2011) 66 Gao et al (2012) 19 Clatts et al (2012) 13 Schneider et al (2012) 18 Yunihastuti et al (2012) 90 Hladik et al (2012) 14 Koblin et al (2013) 24 Sanders et al (2013) 26 Griensven et al (2013) 22 Xu et al (2013) 28 Doerner et al (2013) 21 Zhou et al (2013) 30 van Aar et al (2013) 27 Pando et al (2013) 25 Zeng et al (2014) 32 Sullivan et al (2015) 38 Solomon et al (2015) 37 Liu et al (2015) 34 Sathane et al (2016) 42 Sathane et al (2016) 42 Xu et al (2016) 45 Wang et al (2016) …”
Section: Meta-analysismentioning
confidence: 99%